2007
DOI: 10.1007/s10165-006-0529-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral ureteral stenosis and duodenal perforation in a patient with dermatomyositis

Abstract: We report the case of a 19-year-old man with dermatomyositis who developed abdominal pain and anuria. The examination revealed bilateral ureteral stenosis. The patient also developed multiple ulcerations of the duodenum with perforations. The clinical feature was considered to represent that of juvenile dermatomyositis, which is characterized by systemic necrotizing vasculitis. Rheumatologists should be alerted about this serious complication in patients with childhood or young adult dermatomyositis presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…An emergency operation showed an ulcer and perforation at the junction of the third and fourth portions of the duodenum because of the mesenteric vasculitis [ 16 ]. Rheumatologists should be alerted about this serious complication in patients with childhood or young adult dermatomyositis presenting with abdominal complaints [ 17 ].…”
Section: Acute Intestinal Ischemia In Childrenmentioning
confidence: 99%
“…An emergency operation showed an ulcer and perforation at the junction of the third and fourth portions of the duodenum because of the mesenteric vasculitis [ 16 ]. Rheumatologists should be alerted about this serious complication in patients with childhood or young adult dermatomyositis presenting with abdominal complaints [ 17 ].…”
Section: Acute Intestinal Ischemia In Childrenmentioning
confidence: 99%
“…This leads us to speculate that ureteral stenosis may be related to vasculopathy involving the urinary system. Morita et al [23] reported a case of dermatomyositis who developed duodenal perforation as well as ureteral stenosis, with biopsy of stenotic ureter showing calci cation with granulomatous tissue without any vasculitic lesion. Ruby Haviv et al [24] reported a case of juvenile polymyositis (JPM ) with right ureteral obstruction secondary to necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of ulceration and bleeding perforation of GI tracts in childhood DM is as low as 2-3%, the incidence in adult DM is even lower (~1%) [ 6 ]. The reported sites for GI involvement in adult DM include the esophagus [ 7 9 ], duodenum [ 10 , 11 ], and intestine [ 8 ]. Another example of perforation of the hollow organs is mediastinal emphysema that has originated from a tracheal perforation, which is considered to be related to vasculitis [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%